Local values of Buginese Culture in the practice of government organizations in Sinjai (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
This article aims to analyze the internalization of local values of Bugis culture in the practice of government organizations, as well as the implications of these local values for the public service system. This study uses qualitative research methods, with data collection using observations, interviews, and tracking of related documents. The research location was in the government organization of the Department of Investment and One-Stop Service (Dinas Pelayanan Modal dan Pelayanan Satu Pintu - DPMPS) of Sinjai Regency. The results show that there is an internalization of local values; (1) 'lempu' (honest), (2) 'amaccang' (intelligence), (3) 'astinajang' (propriety), (4) aggatenggeng (firmness), (5) sipakatau and sipakainge, and (6) ajjoareng which have existed since the past and considered to be synergized in the principles of service and apply in the culture of the community that supports the implementation of public services. Then, adopting local values is in line with the principles of good governance namely transparency, accountability and legal certainty. In addition, public administration indicators are oriented to the benefits and effectiveness in achieving goals and as a study of governance and social order.
Keywords: Local wisdom; Bugis culture; government; organization.